2008
DOI: 10.1021/jp802489y
|View full text |Cite
|
Sign up to set email alerts
|

Pt(100)-Catalyzed Ammonia Oxidation Studied by DFT: Mechanism and Microkinetics

Abstract: Density functional theory simulations were used to study the mechanism of ammonia oxidation over Pt(100). The conversion of NH 3 leading to NH x intermediates upon reaction with adsorbed oxygen-containing species and ultimately forming reaction products (NO, N 2 O, N 2 , and H 2 O), have been systematically computed. The reaction proceeds via an imide mechanism, while classical mechanisms postulating nitroxyl and hydroxylamine as reaction intermediates may be excluded. The barriers of oxidative NH 3 dehydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
115
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 58 publications
16
115
1
Order By: Relevance
“…These values agree well with the previously reported results on Pt (100) surface with PW91 functional and (2 9 2) supercell (-3.09, -4.25 and 3.79 eV for atop, bridge and hollow sites, respectively) [45]. Ge et al [46] also theoretically studied the binding energies for a c(2 9 2)-O overlayer on Pt(100)-(1 9 1) surface and concluded that the bridge site possessed the strongest binding, followed by four-fold hollow site, while the atop site was the least stable.…”
Section: Atomic Oxygen (O)supporting
confidence: 93%
“…These values agree well with the previously reported results on Pt (100) surface with PW91 functional and (2 9 2) supercell (-3.09, -4.25 and 3.79 eV for atop, bridge and hollow sites, respectively) [45]. Ge et al [46] also theoretically studied the binding energies for a c(2 9 2)-O overlayer on Pt(100)-(1 9 1) surface and concluded that the bridge site possessed the strongest binding, followed by four-fold hollow site, while the atop site was the least stable.…”
Section: Atomic Oxygen (O)supporting
confidence: 93%
“…Methfessel-Paxton smearing [44] (with N = 1 and s = 0.2 eV) is used for efficiency. We perform calculations for various square supercells with areas 1, 2, 4, 5, 8, 9, and 10 a 2 , where a is the surface lattice constant, corresponding to (1 1), c (22) …”
Section: Theoretical Methods and Key Dft Resultsmentioning
confidence: 99%
“…One might then question the difference in stability for (2 1)(h) and c (22) ordering, where in both cases each oxygen atom is supported by two Pt atoms. However, the weak NN attractions, which are present only in the former case, can explain the enhanced stability.…”
Section: Dft Resultsmentioning
confidence: 99%
See 2 more Smart Citations